FOOD POTENTIAL OF ALTERNATIVE POME FRUIT TREES CULTIVATED IN MOSCOW REGION - EKATERINA V. SOLOMONOVA; NIKOLAI A. TRUSOV; TATIANA D. NOZDRINA; TATIANA P. MEER; VLADIMIR N. SOROKOPUDOV; CECILIA GEORGESCU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The research is aimed at finding new sources of food raw materials for the industrial use at the expense of alternative pome fruit trees (Maleae Small) cultivated in the middle zone of the Russian Federation. The mature fruits of medlar (Mespilus germanica L.), quince (Cydonia oblonga Mill.) and hawthorns (Crataegus submollis Sarg. аnd C. punctata Jacq.) were studied. A rapid analysis of the methods of classical botanical study of morphology, anatomy and morphometry, with the addition of biochemical samples for vitamin C and oil content, was performed. The studied pome fruits are promising for the food use, as well as possibly competitive compared to imported analogues.